Z-Shaped Metasurface-Based Wideband Circularly Polarized Fabry–Pérot Antenna for C-Band Satellite Technology - Nathapat Supreeyatitikul; Akkarat Boonpoonga; Chuwong Phongcharoenpanich (IEEE Access, 2022)
This research proposes a low-profile Z-shaped metasurface (MTS)-based wideband circularly polarized (CP) Fabry–Pérot antenna for C-band satellite communication. The proposed low-cost and low-complexity CP Fabry–Pérot antenna is realized by using three substrate layers: upper, middle, and lower. The substrates are of FR-4 type with a dielectric constant of 4.3 and loss tangent of 0.025. The upper substrate contains 9 × 9 periodically-arranged Z-shaped MTS unit cells functioning as the partially reflecting surface and circular polarization conversion, and at the center of the middle substrate sits a corners-truncated square patch. The lower substrate consists of a copper plate with an H-shaped slot at the center of the ground plane and a microstrip feed line. The lower and middle substrates function as the source antenna. The periodic Z-shaped MTS unit cells are utilized to enhance the impedance bandwidth (IBW) and gain of the source antenna and also to convert linearly polarized into CP wave. The antenna dimension is 1.5λ0 × 1.5λ0 × 0.51λ0. Simulations are performed and experiments carried out. The measured IBW and axial ratio bandwidth are 64% (4.4 – 7.6 GHz) and 18% (4.4 – 5.3 GHz) at the center frequency of 5 GHz. In addition, the proposed antenna scheme achieves a measured 3-dB boresight gain bandwidth of 30% (4.3 – 5.8 GHz) with the maximum gain of 12.88 dBic at 4.7 GHz, rendering the proposed Z-shaped MTS-based CP Fabry–Pérot antenna operationally suitable for satellite communication. In essence, the novelty of this research lies in the use of the low-cost and low-complexity Z-shaped MTS unit cell to effectively enhance the antenna gain and convert LP into CP wave.
Keywords: Advanced Antenna and Metasurface Technologies; Antenna Design and Analysis; Metamaterials and Metasurfaces Applications